Application of agricultural waste activated carbon prepared from sugarcane leaves for methyl orange removal in aqueous solution - Watcharabundit, Prachart; Sawasdee, Dr.Suchada (Food and Applied Bioscience Journal, 2020)
The aim of this work was to prepare activated carbon from sugarcane leaves for methyl orange dye adsorption from aqueous solution. The characterization methods of the adsorbent such as Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Brunauer−Emmett−Teller (BET) were evaluated. Batch adsorption experiments were carried out at varying conditions such as pH (4−10), contact time (5−300 min), adsorbent dose (0.2−1.0 g), initial dye concentration (20−100 mg/L), and temperature (20−40°C). The equilibrium adsorption data were analyzed by Langmuir and Freundlich isotherm models. The kinetic adsorption data were analyzed by pseudo−first order, pseudo-second order, and intra-particle diffusion models. The experimental results showed that the maximum percentage of dye adsorption found at pH 4 was 83.54. The equilibrium adsorption data were fitted well by the Freundlich isotherm, and the maximum adsorption capacity was found to be 12.50 mg/g at 30°C. For the kinetics of adsorption, the data were well described by the pseudo−second−order model at all temperatures. Moreover, the thermodynamic parameter showed that the adsorption process was spontaneous at 40°C and the process was endothermic in nature. The results indicated that the activated carbon could be employed as a low−cost effective adsorbent for dye adsorption from aqueous solution.